Stereomicroscopic Evaluation of the Adaptability Of Different Retro filling Materials (In Vitro Study( (Mustansiria Dental Journal, 2018)
The purpose of this in vitro study was to evaluate the marginal interfaces betweentooth structure and the retro-filling materials.Sixty teeth were divided into six groups of ten for each. The teeth wereinstrumented to a minimum of size no. 45 k-file, obturated with gutta-percha, resectedperpendicular to their long axes and prepared to receive a retro-filling. The teeth werefilled with amalgam, resin-modified GIC or light-cured composite resin. Each fillingmaterial was either applied with dentin adhesive or without dentin adhesive.Photomicrographs were made & examined by four evaluators.Statistical analysis of the results revealed that the composite resin had bettermarginal adaptation than the amalgam & the glass ionomer cement, but the differencewas non significant (p>0.05). In addition, the non-adhesive groups together had lessmarginal adaptation than the other groups and the difference was significant (p